PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA KARYAWAN DI INNA SINDHU BEACH HOTEL - I Nyoman Sudiarta; I Nyoman Surya Saputra (Institut Pariwisata dan Bisnis Internasional, 2016)
Education and employee training that is held at Inna Sindhu Beach Hotel.like Technical skill training, Managerial Skill and other education and skill training, be expected can increase knowledge, skill and attitude of the employee. But for the implementation there are so many obstacles that are found like the limited of budget and follow up in the field is not done well for the control by each department head. The purpose of this research is to know the effect of education and training to employee performance at Inna Sindhu Beach Hotel. Data analysis technique that is used for this research is rank spearman correlation analysis by spreading some questioner in Front office department, Food and beverage service department by using 44 respondent. Sampling technique that is used for this research is non probability sampling with type of saturated sampling by using all of population member. The result of this research show that there is no significant effect p = 0,085 > 0,05 between education and training to employee performance at Inna Sindhu Beach Hotel. Based on the result of the research Hotel side is expected to do education and training more effective, planning the budget to make the education and training can be done continuously, inviting good speaker, making schedule for each employee to follow education and training program and giving the employee matching topic of training with their job.